G275(P) A strategy to support changes in clinical care following training courses at district hospitals in myanmar: implementation plans. (12th March 2018) - Halbert, J; Malley, M; Monaghan, M; Roche, E; Babu, P; Oo, S; Bowyer, J; Wooton, M; Sin, KT
Abstract : Aims: An Emergency Paediatric Care Programme (EPCP) runs training courses in district hospitals. We describe a strategy to support local leadership and develop teams responsible for devising and fulfilling individual implementation plans. Methods: During EPCP courses, participants review the hospital facilities and make recommendations for improvement. A local EPCP Champion (senior clinician) supported by an EPCP Team is responsible for identifying local priorities and developing an Implementation Plan to achieve these. They are asked to consider: layout, infrastructure, staffing, patient safety and infection control, drugs and equipment, staff numbers and training, patient records, clinical guidelines, and morbidity and mortality meetings. Additional support is provided through Global Link Volunteer (GLV) placements in the hospitals. A bi-annual EPCP Champion and Team Conference provides an opportunity to share ideas and experiences, problem solve and discuss quality improvement projects. Results: GLVs, EPCP Champions and Teams representing 7 district hospitals reported on their Implementation Plans at the first EPCP Champion and Team Conference in July 2016. A wide range of topics were described including weekly simulation training, new guideline wall charts, well-equipped resuscitation areas, new admission and observation charts, improved infection control through the repair of broken sinks and provision of hand-gel and multi-disciplinary mortality meetings. Feedback was extremely positive with the teams feeling motivated, empowered and rewarded for their efforts. Conclusions: Successful training depends on its impact in practice; the EPCP Champions and Team Conference demonstrated that the combined efforts of local EPCP Champions and Teams and GLVs in developing the Implementation Plans had led to valuable quality improvements.